Analysis of the fall‐related risk of pharmacotherapy in Czech hospitals: A case control study - Malý, Josef; Doseděl, Martin; Kuběna, Aleš, Antonín; Malá-Ládová, Kateřina; Vosátka, Jan; Brabcová, Iva; Hajduchová, Hana; Bártlová, Sylva; Tóthová, Valérie; Vlček, Jiří (John Wiley & Sons Inc., 2019)
Falls are among the major problems occurring in hospital setting, when drugs are viewed as important modifiable risk factor of falling. The aim was to analyse the effect of pharmacotherapy on the risk of falls in hospitalized patients. Methods A multicentre prospective case‐control study was conducted in 2017 retrieving data from four hospitals in South Bohemia, Czech Republic. An online database was constructed to collect patient and fall‐related data. Each fall that occurred during hospitalization was assigned to appropriate controls (no fall during hospitalization) based on gender, age, length of hospitalization, and the number of drugs. Univariate and multivariate correlations were performed with a significance level of P < .05. Results A total of 222 fall cases (107 males; median age, 81 y) and 1076 controls (516 males; median age, 80 y) were included. According to the first ATC level classification, drugs from groups S, N, and P were significantly associated with fall‐related risk compared with controls (P < .05); further analysis of ATC levels showed that only psycholeptics (N05), antipsychotics (N05A), and tiapride were significantly associated with falls. Regression analysis revealed use of psycholeptics N05 (OR = 2.06; 95% CI, 1.56‐2.76), or ophthalmologicals S01 (OR = 2.72; 95% CI, 1.37‐5.41), as factors with the highest fall‐related risk. Conclusions Apart from the commonly considered fall‐risk increasing drugs, other groups, such as ophthalmologicals, should also be considered; however, regarding clinical practice, it is difficult to evaluate the effects of individual drugs in the context of other risk factors of falls, due to the multifactorial nature of falls.
Analýza farmakoterapie pro riziko pádu v českých nemocnicích: Případová kontrolní studie
Keywords: case‐control study; drug therapy; falls; hospital inpatients; ophthalmologicals; psychoactive drugs; Analýza; farmakoterapie; pro; riziko; pádu; českých; nemocnicích; Případová; kontrolní; studie